The Relationship between Metacognitive Awareness and Receptive Skills of University Students - Ayu Marsela Erda (Lingua Cultura, 2020)
The research investigated the influence of metacognitive awareness on receptive skills in higher education students. Moreover, participants’ level of metacognitive awareness was also taken into account. The research utilized a survey in the form of Metacognitive Awareness Listening Questionnaire (MALQ) and Metacognitive Awareness Reading Strategy Inventory (MARSI) and test of listening and reading comprehension to collect the data and multiple regression to analyze it. The participants were 59 English educational students in the first semester of a public university in Yogyakarta. The finding shows there is a significant influence of metacognitive awareness on receptive skills. However, there is the only significant influence of metacognitive awareness on reading skills. In contrast, there is no significant influence of metacognitive awareness on listening skills. Most of the students are categorized at a high level of metacognitive awareness in listening and reading. However, they have relatively poor scores in the D and E categories for both listening and reading comprehension tests. The only skill which has a significant influence on metacognitive awareness is reading skills. Therefore, the findings show that there is no significant influence of metacognitive awareness on listening skills. However, there is a significant influence of metacognitive awareness on reading skills. Further research needs to be conducted to reveal the different influences between reading and listening skills related to metacognitive awareness, as found in the research.